Rozwiąż równanie :

1. 0,2x + 0,3 = 1,3
2. 5x-0,8 = 0,1 + 2x
3. 8x-0,2 = 8x - 0,1
4. 0,01x + 17 = -0,16x
5 . -0,07(10x-1) = 0,3x
6 . 0,83x+ 0,82 = 0,23x + 1,32
7 . 0,6x + 2(0,1x - 0,1) = 0,2(x+1)
8 . 0,7(x+2 = 0,4(x+1) + 0,3x + 1
9. 0,15(2x+4) = 2(1,3 + 0,3x) - 0,6
10. 0,1(x+1) - 0,005(3x - 10_ = 0,4 - 0,35x

3

Odpowiedzi

2010-02-24T22:52:41+01:00
1. 0,2x + 0,3 = 1,3
0,2x=1,3-0,3
0,2x=1/:0,2
x=5

2. 5x-0,8 = 0,1 + 2x
3x=0,9/:3
x=0,3

3. 8x-0,2 = 8x - 0,1
0=0,1


4. 0,01x + 17 = -0,16x
0,01x+0,16x=-17
0,17x=-17
x=0,01

5 . -0,07(10x-1) = 0,3x
-0,7x+0,07=0,3x
-1,1x=-0,07/:(-1,1)
x=7/110


6 . 0,83x+ 0,82 = 0,23x + 1,32
0,83x-0,23x=1,32-0,82
0,6x=0,5/: (0,6)
x=5/6

7 . 0,6x + 2(0,1x - 0,1) = 0,2(x+1)
0,6x+0,2-0,2=0,2x+0,2
04x=0,2/: (0,4)
x=0,5

8 . 0,7(x+2 = 0,4(x+1) + 0,3x + 1
0,7x+1,4=0,4x+0,4+0,3x+1
0=0

9. 0,15(2x+4) = 2(1,3 + 0,3x) - 0,6
0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=-0,6+2,6-0,6
-0,3x=1,4/:(-0,3)
x=4 całe i 2/3

10. 0,1(x+1) - 0,005(3x - 10_ = 0,4 - 0,35x
0,1x+0,1-0,015x+0,05=0,4-0,35x
0,1x-0,015x+0,35x=0,4-0,05-0,1
0,435x=0,25/:(0,435)
x=87/50


14 4 14
Najlepsza Odpowiedź!
2010-02-24T22:59:11+01:00
1.
0,2x + 0,3 = 1,3
0,2x = 1,3 - 0,3
0,2x = 1/:0,2
x = 5

2.
5x - 0,8 = 0,1 + 2x
5x - 2x = 0,1 + 0,8
3x = 0,9/:3
x = 0,3

3.
8x - 0,2 = 8x - 0,1
8x - 8x = - 0,1 + 0,2
= 0,1

4.
0,01x + 17 = - 0,16x
0,01x + 0,16x = -17
0,17x = -17/:0,17
x = -100

5.
-0,07 (10x - 1) = 0,3x
-0,7x + 0,07 = 0,3x
-0,7x - 0,3x = - 0,07
-x = - 0,07/:(-1)
x = 0,07

6.
0,83x + 0,82 = 0,23x + 1,32
0,83x - 0,23x = 1,32 - 0,82
0,6x = 0,5/:0,6
x = ⅚

7.
0,6x + 2(0,1x - 0,1) = 0,2(x+1)
0,6x + 0,2x - 0,2 = 0,2x + 0,2
0,8x - 0,2x = 0,2 + 0,2
0,6x = 0,4/:0,6
x = ⅔

8.
0,7(x+2) = 0,4(x+1) + 0,3x + 1
0,7x + 1,4 = 0,4x + 0,4 + 0,3x + 1
0,7x - 0,4x - 0,3x = 1,4 - 1,4
0 = 0

9.
0,15(2x+4) = 2(1,3 + 0,3x) - 0,6
0,3x + 0,6 = 2,6 + 0,6x - 0,6
0,3x - 0,6x = 2 - 0,6
-0,3x = 1,4/:(-0,3)
x = -4⅔

10.
0,1(x+1) - 0,005(3x - 10) = 0,4 - 0,35x
0,1x + 0,1 - 0,015x + 0,05 = 0,4 - 0,35x
0,085x + 0,35x = 0,4 - 0,1 - 0,05
0,435x = 0,25/:0,435
x = ⁵⁰/₈₇

;-))
39 4 39
2010-02-24T23:05:50+01:00
1. 0,2x + 0,3 = 1,3
0,2x=1,3-0,3
x=5

2. 5x-0,8 = 0,1 + 2x
3x=0,9
x=0,3

3. 8x-0,2 = 8x - 0,1
0x=0,1
x=0

4. 0,01x + 17 = -0,16x
0,17x=-17
x=100

5 . -0,07(10x-1) = 0,3x
-0,7x-0,07=0,3x
-x=0,07
x=-0,07

6 . 0,83x+ 0,82 = 0,23x + 1,32
0,6x=0,5
x=0,83

7 . 0,6x + 2(0,1x - 0,1) = 0,2(x+1)
0,6x+0,2x-0,2x=0,2+0,2
0,6x=0,4
x=0,6
8 . 0,7(x+2 = 0,4(x+1) + 0,3x + 1
0,7x+1,4=0,4x+0,4+0,3x+1
0x=0
x=0

9. 0,15(2x+4) = 2(1,3 + 0,3x) - 0,6
0,3x+0,6=2,6+0,6x-0,6
-0,3x=1,4
x=-4,6

10. 0,1(x+1) - 0,005(3x - 10_ = 0,4 - 0,35x
0,1x+0,1-0,015x-0,05=0,4-0,35x
0,435x=-0,35
x=-0,80
8 4 8